Multi-omics analysis revealed the role of CCT2 in the induction of autophagy in Alzheimer’s disease - Ma, Xueting; Feng, Yuxin; Quan, Xiangyu; Geng, Bingyu; Li, Guodong; Fu, Xueqi; Zeng, Linlin (Frontiers in Genetics, 2023)
Chaperonin containing TCP1 subunit 2 (CCT2) is essential in various neurodegenerative diseases, albeit its role in the pathogenesis of Alzheimer's disease (AD) remains elusive. This study aimed to evaluate the role of CCT2 in AD. First, bioinformatics database analysis revealed that CCT2 was significantly downregulated in patients with AD and associated with autophagic clearance of β-amyloid. The 789 differentially expressed genes overlapped in AD-group and CCT2-low/high group, and the CCT2-high-associated genes screened by Pearson coefficients were enriched in protein folding, autophagy, and messenger RNA stability regulation pathways. These results suggest that CCT2 is significantly and positively associated with multiple pathways linked to autophagy and negatively associated with neuronal death. The logistic prediction model with 13 key genes, such as CCT2, screened in this study better predicts AD occurrence (AUC=0.9671) and is a favorable candidate for predicting potential biological targets of AD. Additionally, this study predicts reciprocal micro RNAs and small molecule drugs for hub genes. Our findings suggest that low CCT2 expression may be responsible for the autophagy suppression in AD, providing an accurate explanation for its pathogenesis and new targets and small molecule inhibitors for its treatment.